2011
DOI: 10.5103/kjsb.2011.21.1.067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on Gait Patterns of the Elderly and the Young Regarding to Foot Pressure

Abstract: The purpose of this study was to find the difference in gait patterns when elderly and young people walk by analyzing COP, Gait Line, Foot pressure pattern, and ensuring the original biomechanics technology of developing high performance footwear for the elderly.The subjects who took part in the test consist of 20 elderly people and 20 young people. The physical features of the elderly people that were recruited for the study are as below: 20 healthy male subjects(elderly people) with an average age of 75.43 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…For the results in the MF and HF regions, the mean force, peak pressure, and contact area measured in the OT and UT all increased. Previous studies analyzing the gait characteristics of the elderly reported an increase in support time and a decrease in movement speed from the initial stance phase to the middle stance phase for stable gait [43]. Accordingly, it could be confirmed that total plantar pressure distribution, not local pressure, increased while using the cautious gait strategy to stably maintain dynamic balance in an environment with obstacles or uneven ground.…”
Section: Discussionmentioning
confidence: 68%
“…For the results in the MF and HF regions, the mean force, peak pressure, and contact area measured in the OT and UT all increased. Previous studies analyzing the gait characteristics of the elderly reported an increase in support time and a decrease in movement speed from the initial stance phase to the middle stance phase for stable gait [43]. Accordingly, it could be confirmed that total plantar pressure distribution, not local pressure, increased while using the cautious gait strategy to stably maintain dynamic balance in an environment with obstacles or uneven ground.…”
Section: Discussionmentioning
confidence: 68%